Species distribution and antimicrobial susceptibility pattern of coagulase-negative staphylococci isolated from clinical specimens at a tertiary care hospital - Sabiha S Tamboli; Saleem B Tamboli (IMC Journal of Medical Science, 2023)
Background and objectives: Coagulase-negative staphylococci (CoNS) are considered important causative agents of hospital acquired infection. These organisms are found in various clinical specimens from hospitalized patients. Present study was carried out to determine the species distribution and antimicrobial susceptibility pattern of CoNS isolated from clinical specimens at a tertiary care hospital.